Identification and Quantification of Fatty Acid Profile of Muscle and Gametes in Threatened Abant Trout (Salmo abanticus) from Wild - Ozcicek, Esin; Kocabas, Filiz Kutluyer; Kocabas, Mehmet; Yilmaz, Okkes (Pleiades Publishing Inc, 2025)
As an important challenge restricting hatchery production, gamete quality and subsequent larvae and juvenile are influenced by broodstock nutritional status (i.e., protein, essential amino acids, fatty acid profile and minerals). Hence, the fatty acid (FA) profiles of muscle and gametes in threatened Abant trout (Salmo abanticus) from wild was elucidated and quantitated using the gas chromatography. Our results indicated that the saturated fatty acids (SFAs) in muscle and sperm (38.00 and 60.98%) of S. abanticus occurred in higher quantities than unsaturated fatty acids. The egg of S. abanticus in the wild is characterized by high (mostly n-6 HUFA, 33.59%). Tricosanoic acid (C23:0) and docosahexaenoic acid (DHA, C22:6 n-3) were not determined in sperm of S. abanticus. Overall, the current study provides FA composition in the reproduction cells and muscle of mature S. abanticus and the gametes and muscle had similar general FA profiles with the dominance of C18:1 n-9 (Oleic acid), C16:0 (Palmitic acid), C4:0 (Butyric acid), C18:2 n-6 (Linoleic acid, LA) and C20:5 n-3 (Eicosapentaenoic acid, EPA).
Keywords: fatty acid; Abant trout; Salmo abanticus; sperm; egg; muscle